Penetapan Kadar Flavonoid Total dan Uji Daya Antioksidan Ekstrak Etanol Daun Ungu (Graptophyllum Pictum L.) Griff ) - Haeria Haeria (Universitas Islam Negeri Alauddin Makassar, 2013)
A study concerning determination of total flavanoid content, and antioxidant activity of ethanolic extract daun ungu (Graptophyllum pictum (L.) Griff). The purpose of this study was to determine the levels of total flavonoids and reduction power test of ethanolic extract daun ungu (Graptophyllum pictum (L.) Griff). Extraction of chemical constituents from the daun ungu (Graptophyllumpictum (L.) Griff) by maceration method using ethanol 70%. To determine the levels of flavonoids and reduction power of the extract samples, then analyzed using a spectrophotometer UV-Vis compound. The result showed levels of total flavonoids purple leaf (Graptophyllum pictum (L.) Griff) from a concentration of 2%, 3%, 4%, 5% and amounted to 6,293 mg/100 g, 7,856 mg/100 g, 8,335 mg/100 g and 8,852 g. In the determination of reducing power of ethanolic extract daun ungu (Graptophyllum pictum (L.) Griff) had a reduced ability at 2%, 3%, 4%, 5% concentration and amounted to 5,65 mg/100 g, 14,73 mg/100 g, 17,70 mg/100 g and 21,60 mg/100 g. Reduction power ethanol extract of purple leaf was increase with increasing concentration, the higher concentration have more potent extract reduction capability.